Sechenov University and Izhevsk Radio Plant Entered into an Agreement on the Development and Production of a Domestic Device for Diagnosing Bacterial Overgrowth - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.